2016
DOI: 10.2214/ajr.14.14101
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Volume Navigation Technique for Combining Real-Time Ultrasound and Contrast-Enhanced MRI: Accuracy and Feasibility of a Novel Technique for Locating Breast Lesions

Abstract: The volume navigation technique is an accurate method for coregistration of CE-MRI and sonographic images, enabling lesion localization within a limited volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Recently, image fusion techniques have been investigated to create navigable anatomy reconstructions that enable the visualization of MRI-detected lesions on real-time US images [3]. Both commercial and research platforms that implement this strategy align the two images by computing either rigid or affine transformation which minimizes the matching error between sets of corresponding landmarks [4,5]. The main limitation of this approach is that it does not account for the highly deformable nature of the breast.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, image fusion techniques have been investigated to create navigable anatomy reconstructions that enable the visualization of MRI-detected lesions on real-time US images [3]. Both commercial and research platforms that implement this strategy align the two images by computing either rigid or affine transformation which minimizes the matching error between sets of corresponding landmarks [4,5]. The main limitation of this approach is that it does not account for the highly deformable nature of the breast.…”
Section: Introductionmentioning
confidence: 99%
“…Limitations of volume navigation technique are associated with errors in coregistration of MR dataset and live US because it is primarily based on the assumption that the structures within the data volume (i.e., the body part studied) have fixed positions, relative to each other, in the two different imaging modalities [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, as previously noted, breast tissues are soft and easily deformable so that they can undergo relevant modifications from prone to supine position, thus causing discrepancies and misalignment in coregistration. Compensation algorithms for such causes of misalignment have been proposed, but they are still limited in medical applications because of the complex physical properties of tissues [ 46 ]. Another important factor which may reduce the effectiveness of US-MR coregistration is breast hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, an MRI to US breast study also used three external markers at those approximate locations and found improvement in lesion registration. 35 Intuitively, one would suspect that more external markers would allow for better correlation. However, this study indicates that when modeling large breast compressions, external deformation may not be completely indicative of internal breast deformation.…”
Section: Without Marker Analysismentioning
confidence: 99%